Type 1 diabetes, COVID‐19 vaccines and short‐term safety: Subgroup analysis from the global COVAD study - Tulika Chatterjee; Naveen Ravichandran; Narmadha Nair; Abraham Edgar Gracia‐Ramos; Bhupen Barman; Parikshit Sen; Mrudula Joshi; Sreoshy Saha; Arvind Nune; Arun Kumar R Pande; Tsvetelina Velikova; Ioannis Parodis; et al. (Journal of Diabetes Investigation, 2024)
Abstract Aims/Introduction Coronavirus disease 2019 (COVID‐19) vaccinations have been proven to be generally safe in healthy populations. However, the data on vaccine safety in patients with type 1 diabetes are scarce. This study aimed to evaluate the frequency and severity of short‐term (<7‐day) adverse vaccination events (AEs) and their risk factors among type 1 diabetes patients. Materials and Methods This study analyzed data from the COVID‐19 vaccination in Autoimmune Diseases (COVAD) survey database (May to December 2021; 110 collaborators, 94 countries), comparing <7‐day COVID‐19 vaccine AE among type 1 diabetes patients and healthy controls (HCs). Descriptive statistics; propensity score matching (1:4) using the variables age, sex and ethnicity; and multivariate analyses were carried out. Results This study analyzed 5,480 completed survey responses. Of all responses, 5,408 were HCs, 72 were type 1 diabetes patients (43 females, 48.0% white European ancestry) and Pfizer was the most administered vaccine (39%). A total of 4,052 (73.9%) respondents had received two vaccine doses. Patients with type 1 diabetes had a comparable risk of injection site pain, minor and major vaccine AEs, as well as associated hospitalizations to HCs. However, type 1 diabetes patients had a higher risk of severe rashes (3% vs 0.4%, OR 8.0, 95% confidence interval 1.7–36), P = 0.007), although reassuringly, these were rare (n = 2 among type 1 diabetes patients). Conclusions COVID‐19 vaccination was safe and well tolerated in patients with type 1 diabetes with similar AE profiles compared with HCs, although severe rashes were more common in type 1 diabetes patients.